PECS (Picture Exchange Communication System) Terhadap Keterampilan Sosial Anak ADHD (Attention Deficit-Hyperactive Disorder) - Sari, Virgian Ferda; Sukerti, Ni Wayan (JPK (Jurnal Pendidikan Khusus), 2020)
This research aimed to identify the effects of PECS on the social skills of a student with ADHD, who experienced delayed in communication and social interaction. This research used Single Subject Design, with A-B-A design as the research design. The data were presented using graphics and analyzed using visual analysis. The subject of this research was a first grader with ADHD in an Inclusive Elementary School.  The result of this research showed that there was an effect on the implementation of PECS on the social skill of a student with ADHD; the student's tendency to refuse the invitation to play together with others decreased. Moreover, the implementation of PECS enabled the student to understand the kinds of social skills that could be done together through PECS's interactive pictures. Furthermore, it was found that PECS could optimize the student's communicative and cognitive aspects.